Statins and immunotherapy: Togetherness makes strength The potential effect of statins on immunotherapy for NSCLC. Issue 4 (31st March 2021) - Rossi, Alessandro; Filetti, Marco; Taurelli Salimbeni, Beatrice; Piras, Marta; Rizzo, Francesco; Giusti, Raffaele; Marchetti, Paolo
Abstract: Background: Recent researches suggested that statins, beside their role in inhibiting endogenous cholesterol synthesis and in cardiovascular prevention, could influence several processes in cancer biology. In fact, a recent meta‐analysis demonstrated that statins could positively influence OS in lung cancer patients. Aim: There is a lack of large cohort studies that could support a potential antineoplastic role of statins in clinical practice. We collected data from 162 patients treated with immunotherapy for Nonsmall Cell Lung Cancer (NSCLC) in first‐ and second‐line setting to investigate the impact of these drugs on survival parameters. Methods and Results: In our observational study, we enrolled 162 patients who received immunotherapy for lung cancer between October 2015 and April 2020. We used descriptive statistics to analyze patients' baseline features. Tumor response was evaluated using RECIST version 1.1 guidelines. Uni and multivariate analysis were conducted to investigate the relationship between statin use and response to immunotherapy, using the χ 2 ‐test. We used Kaplan‐Meier curves to estimate OS and PFS in statin and nonstatin users. We included 122 patients in the final analysis. Median PFS was 17.57 months in the statin group and 9.57 months in the nonstatin group, with a P  = <.001. Moreover, median OS was superior in the statin‐users group, with a statistically significant difference (19.94 vs 10.94 months, P  = <.001). Conclusion: Although in our study, statin use positively correlates with PFS and OS in lung cancer patient treated with immunotherapy, these results require a further validation with randomized clinical trials.